Werkstätten oder Wohnhäuser? Ein Beitrag zur Ansprache und Deutung von wikingerzeitlichen Grubenhäuser - Schade, Tobias (Arkæologi i Slesvig-Archäologie in Schleswig, 2020)
In the area between the Eider and the Kongeå, many Viking Age settlements are known, but only at fifty-seven sites could structures of buildings be identified. Thirty-four settlements contained pit-houses, but in some cases the dominance of pit-houses over post built structures was striking. Settlement sites with predominantly sunken-featured buildings are often interpreted as seasonal settlements, trading places, or specialised settlement sites. However, historical analogies indicate a possible function of the sunken-featured as living areas in which daily activities such as sleeping, cooking, handling of refuse, or handicrafting took place. The analysis of features from the settlement of Kosel-East (LA 198), distr. Rendsburg-Eckernförde, yields evidence on economic activities in some of the longhouses as well as on the habitation of some pit-houses. Sometimes it is assumed that pit-houses with fireplaces could have been used for living or they were used as outbuildings. In the scientific discussion, however, longhouses are defined as habitable in contrast the use of the pit-houses which is often identified as seasonal or for skilled crafts. But only in two cases it was possible to identify workplaces situated in pit-houses in Kosel-East. On the other hand, many pit-houses built in robust techniques and with fireplaces inside implied a theoretical habitability. In combination with the evidence of objects of daily use or indicators for a domestic economy disposed in abandoned pit-houses and pits, possible areas of activity e. g. housing space could be identified. Referring to other historical and archaeological analogies, this paper offers a theoretical and methodological contribution to the discussion of the housing situation, emphasizing different archaeological indications for the identification of various (hybrid) ways of living and working.